Effect of the Extracts of Sargassum fusiforme on Red Tide Microalgae in East China Sea - Zhang, Yurong; Xu, Nianjun; Li, Yahe (Frontiers in Marine Science, 2021)
This study examined the effects of extracts of hijiki (Sargassum fusiforme) on the growth and physiology of three species of red tide microalgae (Prorocentrum donghaiensis, Skeletonema costatum and Heterosigma akashiwo) that commonly grow in the East China Sea. The red tide algae were cultivated with the hijiki extracts at different concentrations to investigate the effects of the extracts on cells growth, chlorophyll a content, maximum quantum yield of PSII (Fv/Fm), the activities of four oxidoreductases including peroxidase (SOD), glutathione S-transferase (GST), glutathione peroxidase (GSH-Px), glutathione reductase (GR), and the level of the membrane lipid peroxidation product, malondialdehyde (MDA). The sensitivity of red tide algae to the extracts varied among the strains, with P. donghaiensis being the most sensitive, followed by S. costatum, and then H. akashiwo. Furthermore, the extracts had a rapid lethal effect on P. donghaiensis at over 1.6 g/L and on S. costatum and P. donghaiensis at over 8 g/L. From that concentration, increasing amounts of the extracts in cultures of S. costatum promoted a reduction in Chla contents and Fv/Fm values. In addition, the oxidoreductase activity of S. costatum was reduced at 4 g/L and 6 g/L, as shown by the reduced activity of SOD, GR, GSH-Px, GST and MDA content in the cells. The results presented herein will be useful to the development and utilization of hijiki on red tide control, and marine environmental protection.